Peningkatan Literasi Keuangan Syariah Masyarakat Desa dalam Mencapai Ekonomi Inklusif Menuju Kesejahteraan Masyarakat: Pembangunan Ekonomi, Kelembagaan, dan Kewirausahaan - Agus Suman; Indri Supriani; Yendi Rio Nurrachman (Jurnal Pengabdian kepada Masyarakat, 2024)
Financial literacy, including sharia financial literacy, is one of the keys to the growth and development of an economy. As the country with the largest Muslim population in the world, Indonesia has great potential to utilize Islamic finance as a support for economic development. Thus, the Indonesian government is encouraging an increase in financial literacy, not only in conventional finance but also in sharia finance. Sharia economic, financial, and banking services in Indonesia have experienced a rapid increase, marked by the number of Sharia banks showing a positive trend. However, more than 80 million Indonesians are categorized as unbanked amid sharia financial services development. Therefore, sharia financial literacy education is needed to increase sharia financial literacy. This service activity aims to provide outreach and education regarding Sharia financial institutions, types, and services. This service activity is essential to carry out by considering village communities' low literacy level and financial inclusion. The service activities are in Ngaglik Village, Sengat District, Blitar Regency, East Java. Thus, Sharia financial education is expected to encourage increased involvement of MSME players in Sharia financial services, including obtaining business capital financing. Keywords: Sharia Financial Literacy, Sharia Financial Inclusion, MSMEs, Inclusive Economy, Welfare.